2002
DOI: 10.1017/s0265021502000157
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation anaesthesia is cost-effective for ambulatory surgery: a clinical comparison with propofol during elective knee arthroscopy

Abstract: For this patient group, use of inhalation anaesthesia reduced drug costs by half and shortened emergence times compared to target controlled infusion with propofol with equal perioperative patient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…In addition, TCI uses averaged pharmacokinetic models to control the infusion rate to regulate the calculated plasma concentration, rather than indirect control by adjusting the infusion rate [45], so the awakening time can be predicted [34]. Two studies have demonstrated that DES anesthesia shortened extubation time compared to TCI with propofol [8,46]. However, in these studies, nitrous oxide was used as an adjuvant to the anesthetics, which reduced the requirement of DES during the maintenance period and facilitated emergence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TCI uses averaged pharmacokinetic models to control the infusion rate to regulate the calculated plasma concentration, rather than indirect control by adjusting the infusion rate [45], so the awakening time can be predicted [34]. Two studies have demonstrated that DES anesthesia shortened extubation time compared to TCI with propofol [8,46]. However, in these studies, nitrous oxide was used as an adjuvant to the anesthetics, which reduced the requirement of DES during the maintenance period and facilitated emergence.…”
Section: Discussionmentioning
confidence: 99%
“…The drug-related costs have been shown to be lower compared with intravenous techniques, especially when taking drug waste into account. [10][11][12] Although the cost of anesthesia constitutes only a small proportion of total costs associated with surgery, anesthetic drug expenditures have been a focus of increasingly important cost-containment efforts. Low-flow anesthesia is a simple method of reducing the consumption of volatile agents during inhalational anesthesia.…”
Section: Cost Benefit From Reducing Fresh Gas Flowmentioning
confidence: 99%
“…They found that desflurane was faster at controlling hemodynamic response to painful stimulation at 1 as well as 3 LÁmin -1 fresh gas flow. At 1 LÁmin -1 , the average time to control the MAP was significantly shorter with desflurane [17 (12) min] than with isoflurane [29 (16) min], with 60% of the patients in the isoflurane group requiring rescue therapy. De Baerdemaeker et al 55 studied fifty morbidly obese patients undergoing laparoscopic gastroplasty who received BIS-guided sevoflurane or desflurane anesthesia in combination with a remifentanil target-controlled infusion.…”
Section: Alveolar Ventilationmentioning
confidence: 99%
“…Patients were randomised by the envelope technique into two groups of 15 patients each. In the control group desflurane concentration was adjusted according to routines at the department, and clinical judgement was based on the Evans scoring system which includes heart rate, blood pressure, sweating and tears (10). The goal was to maintain heart rate and blood pressure within ±15% from baseline and to avoid tearing and sweating (AAI™ was not monitored).…”
Section: Methodsmentioning
confidence: 99%